CLASSICAL GERMAN LITERATURE IN THE EDUCATIONAL STANDARD OF AZERBAIJAN - Yusifli, Arzu; Allahverdiyeva, Ayshan (SWorldJournal, 2024)
German literature in Azerbaijan’s educational program is primarily integrated within foreign language studies, especially for students selecting German as a second or third language. In secondary schools and universities, it is included in language cours